Promoting the market and system integration of renewable energies through premium schemes: A case study of the German market premium - Erik Gawel; Alexandra Purkus (Helmholtz-Zentrum für Umweltforschung (UFZ), 2013)
With the share of renewable energies within the electricity sector rising, improving their market (i.e. inclusion in the allocative processes of the electricity market) and system integration (i.e. enhanced responsibility for grid stability) is of increasing importance. To transform the energy system efficiently while ensuring security of supply, it is necessary to increase the alignment of renewable electricity production with short- and long-term market signals. By offering plant operators a premium on top of the electricity market price, premium schemes represent a potential option for achieving this, and have been implemented by several EU member states. This paper focuses on the case study of the German market premium scheme, which has been adopted as part of the 2012 amendment of the Renewable Energy Sources Act. Building on an evaluation of early experiences, we discuss whether the market premium in its current design improves market and/or system integration, and if it seems suitable in principle to contribute to these aims (effectiveness). Also, potential efficiency gains and additional costs of administering integration are discussed (efficiency). While market integration in a narrow sense (i.e. exposing renewables to price risks) is not the purpose of the German premium scheme, it has successfully increased participation in direct marketing. However, windfall profits are high, and the benefits of gradually leading plant operators towards the market are questionable. Incentives for demand-oriented electricity production are established, but they prove insufficient particularly in the case of intermittent renewable energy sources. It seems therefore unlikely that the German market premium scheme in its current form can significantly improve the market and system integration of renewable energies. To conclude, we provide an outlook on alternative designs of premium schemes, and discuss whether they seem better suited for addressing the challenges ahead.
Keywords: H23; Q42; Q48; 330; Renewable Energies; Market Integration; System Integration; Market Premium; Renewable Energy Sources Act (EEG); Efficiency